Structural Modeling of Elastoplastic Deformation Processes of the Bodies of Non-classical Shape - Sizova, N. D. (NTU "KhPI", 2016)
An approach based on the theory of small elastoplastic deformations is proposed to study the aims of the stress-strain state determining of finned cylindrical and conical bodies of finite sizes. We consider small elastoplastic deformations described by the nonlinear equations system, for linearization of which the variable elastic parameters method is applied. Approximate solution of the linearized elasticity problem at each k-th iteration is made with the use of the R-functions theory in the form of a single analytical expression. Determination of the stress-strain state, the plasticity areas and analysis of the results obtained has been performed with the POLE software package.
Keywords: elasticity; small elastoplastic deformations; R-functions